Effect of high salinity and of priming of non-germinated seeds by UV-C light on photosynthesis of lettuce plants grown in a controlled soilless system - Fgaier, Salah; Aarrouf, Jawad; Lopez-Lauri, Félicie; Lizzi, Yves; Poiroux, Florine; Urban, Laurent (Frontiers in Plant Science, 2023)
High salinity results in a decrease in plant photosynthesis and crop productivity. The aim of the present study was to evaluate the effect of UV-C priming treatments of lettuce seeds on photosynthesis of plants grown at high salinity. Non-primed and primed seeds were grown in an hydroponic system, with a standard nutrient solution, either supplemented with 100 mM NaCl (high salinity), or not (control). Considering that leaf and root K + concentrations remained constant and that chlorophyll fluorescence parameters and root growth were not affected negatively in the high salinity treatment, we conclude that the latter was at the origin of a moderate stress only. A substantial decrease in leaf net photosynthetic assimilation (Anet) was however observed as a consequence of stomatal and nonstomatal limitations in the high salinity treatment. This decrease in Anet translated into a decrease in growth parameters; it may be attributed partially to the high salinity-associated increase in leaf concentration in abscisic acid and decrease in stomatal conductance. Priming by UV-C light resulted in an increase in total photosynthetic electron transport rate and Anet in the leaves of plants grown at high salinity. The increase of the latter translated into a moderate increase in growth parameters. It is hypothesized that the positive effect of UV-C priming on Anet and growth of the aerial part of lettuce plants grown at high salinity, is mainly due to its stimulating effect on leaf concentration in salicylic acid. Even though leaf cytokinins' concentration was higher in plants from primed seeds, maintenance of the cytokinins-to-abscisic acid ratio also supports the idea that UV-C priming resulted in protection of plants exposed to high salinity.